The Beldonald Holbein - James, Henry, 1843-1916 (Salt Lake City, UT : Project Gutenberg, 2000)
"The Beldonald Holbein" by Henry James is a novel written in the early 20th century. The book revolves around themes of beauty, perception, and the complexities of social relationships, particularly focusing on the character of Lady Beldonald and her connections to beauty and vanity. It explores the nuances of identity and status in the context of society and art. The story begins with an intriguing proposition to the painter, who is asked to create a portrait of Lady Beldonald, a beautiful but somewhat confused American widow living in London. As the narrative unfolds, it delves into Lady Beldonald's relationship with her companion, Mrs. Brash, who appears plain but ultimately reveals a hidden beauty that contrasts sharply with the societal expectations placed on them. The painter becomes ensnared in the complicated dynamics between the two women, prompting him to reflect on the nature of beauty and the cost that comes with it. Through the interactions and revelations about the characters, the novel examines the poignant themes of identity, appreciation, and the roles women play in the shadows of societal norms. (This is an automatically generated summary.)
Release date is 2000-10-01
Transcribed from the 1922 Macmillan and Co. edition by David Price. Proofing by Andy and his wife
Keywords: London (England) -- Fiction; Cousins -- Fiction; Artists -- Fiction; Artists' models -- Fiction; Portrait painters -- Fiction